A UV-induced mutant of Cryptococcus flavus GB-1 with increased production of a biodegradable plastic-degrading enzyme. Issue 11 (November 2015) - Watanabe, Takashi; Suzuki, Ken; Shinozaki, Yukiko; Yarimizu, Tohru; Yoshida, Shigenobu; Sameshima-Yamashita, Yuka; Koitabashi, Motoo; Kitamoto, Hiroko K.
Graphical abstract: Highlights: Cryptococcus flavus GB-1 produces CfCLE that efficiently degrades biodegradable plastics. The CfCLE-encoding gene, CfCLE1 was obtained and sequenced. A CfCLE productivity enhanced mutant C. flavus GB-1-DMC1 was obtained. Xylose-fed batch cultivation using a jar fermentor was useful to scale-up CfCLE production. CfCLE degraded various BPs cast films. Abstract: The yeast strain, Cryptococcus flavus GB-1, isolated from rice husks as a candidate producer of a biodegradable plastic (BP)-degrading enzyme. The genomic DNA sequence encoding the BP-degrading enzyme of GB-1 was determined. The enzyme was named CfCLE because the deduced amino acid sequence (239 amino acids) was found to be 93% identical to that of CLE of Cryptococcus sp. S-2 (accession No.BAK82405.1 ). The strain GB-1 forms a clear zone (halo) around its colonies on emulsified polybutylene succinate- co -adipate (PBSA) agar plates containing soybean oil but not on plates containing glucose. A UV-induced mutant from this strain, designated as GB-1-DMC1, formed halos on emulsified PBSA plates containing glucose and showed 1.53 U/ml of PBSA-degrading activity in liquid culture with glucose, which was more than 2.5-fold higher than that of the parent strain GB-1 (0.58 U/ml). Moreover, using xylose as a carbon source enhanced the PBSA-degrading activity of both strains. Xylose fed-batch cultivation of GB-1 and GB-1-DMC1 using a 5-l jar fermentor for 72 h produced 12.1 and 21.2 U/ml of CfCLE, respectively. Purified CfCLE has a molecular mass of 22 kDa, and its optimal pH and temperature for enzyme activity is 7.8 and 45 °C, respectively. CfCLE degraded various BP cast films.